2020
DOI: 10.3389/fpsyt.2020.00395
|View full text |Cite
|
Sign up to set email alerts
|

The Accessibility of Opioid Agonist Treatment and Its Forced Discontinuation in Swiss Prisons—Attitudes, Perceptions and Experiences of Defense Lawyers in Dealing With Detained Persons Using Opioids

Abstract: Background: Opioid agonist treatment (OAT) is an important pillar in the treatment of individuals using opioids and its continuation during imprisonment is recommended. Despite this knowledge access to and continuation of OAT is still limited in many countries. The forced discontinuation during pre-trial detention can cause severe withdrawal symptoms, which in turn may significantly impair the defendant's ability to exercise granted procedural participation rights. Furthermore, it can be argued that forced dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The research team itself had gathered previous experience in employing qualitative research methodology on perceptions toward ADHD, SUD, and psychosis among the general population, medical and legal experts and affected individuals. Results have been reported elsewhere ( 22 , 35 38 ).…”
Section: Methodsmentioning
confidence: 53%
See 3 more Smart Citations
“…The research team itself had gathered previous experience in employing qualitative research methodology on perceptions toward ADHD, SUD, and psychosis among the general population, medical and legal experts and affected individuals. Results have been reported elsewhere ( 22 , 35 38 ).…”
Section: Methodsmentioning
confidence: 53%
“…Since almost all respondents experienced the care of detainees with ADHD as labor- and time-intensive, energy-consuming and generally exhausting, and had adopted the view that inmates suffering from this disorder were in need of specific interventions, support and treatment, we are cautiously optimistic that at least in comparable penal institutions, staff may be open to the implementation of non-pharmacological treatments, offender psychoeducation and psychological treatment programs such as Reasoning and Rehabilitation 2 ADHD ( 88 ). In order to develop the understanding and acceptance of stimulant treatment for inmates with ADHD, it might be helpful to point to the successes of other pharmaceutical treatments for mental disorders, which were once considered highly controversial, but are generally better accepted today by prison staff ( 22 ). In addition, public opinion also seems to be changing regarding the use of psychotropic medications in cases of mental illness, as recently pointed out by Angermeyer et al who reported that attitudes toward pharmacological treatment have become noticeably more favorable over the last two decades ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there are studies that show that the real possibilities of care for inmates with ADHD are very limited, both in terms of access to diagnostic assessment and initiation of multimodal treatment (Berryessa, 2017; Hall & Myers, 2016; Susan Young, Gudjonsson, et al, 2018). In addition, it has been observed in everyday clinical practice that the continuation of pharmacological therapy for patients treated with stimulants before imprisonment is also extremely complicated and unlikely (Anna Buadze et al, 2020). This lack of care may reflect the challenges faced by those working in the prison system against the background of the comorbidities (conduct disorder, antisocial personality traits or disorder, comorbid substance use disorder) frequently encountered among inmates with ADHD (Hall & Myers, 2016).…”
Section: Introductionmentioning
confidence: 99%